Sistema de protección inteligente contra perturbaciones eléctricas - Ovando-Chajón, Sergio Eduardo (Instituto Tecnológico de Costa Rica, 2000)
Power quality, an international concept that has the main purpose to minimize electrical disturbances, the ones coming from the power supplier and the ones produced by the supplier’s customers. Permanent monitoring and measurement of electrical quantities, at low cost and as effective as possible of the power network, power supply of floor equipment, computer equipment and all those devices susceptible to electrical disturbances. It is required to have a high end, real time analysis and data interpretation of electrical power events. The system must have communications with other devices that could handle data management, data storage and graphical display of trends and data logging. To reach the power quality’s level, in which all the parts involved have to join forces in order to have a good performance of productivity means and power supply, it is required the market to have an idea of electrical improvement. Elvatron S.A. had the idea to improve a power monitoring, measurement and control system of electrical distortions, in order to offer another effective, low cost, high quality product to its customers. This system uses international high quality products from Rockwell Automation and Allen-Bradley’s stock. This brings up an intelligent system against electrical disturbances called SPICPE, that has the main purpose to monitor and measure electrical parameters, with system integration to a programmable logic controller based central module, with computer background. This is the result of the analysis of customer’s demands, competition and requirements of Elvatron.
Proyecto de Graduación (Bachillerato en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2000.
Keywords: Códigos; Módulos; Comunicación; Monitoreo; Software; Usuario